Project-Based Learning on Laboratory Experiment about Refraction and Total Internal Reflection of Different Types of Materials - Ahmad Swandi; Sri Rahmadhanningsih; Bunga Dara Amin; Nurhayati Nurhayati; Sparisoma Viridi; Chi-Hung Chang (JIPF (Jurnal Ilmu Pendidikan Fisika), 2022)
The use of Project-Based Learning (PjBL) in Physics Learning has been widely used, but only as a learning model that is used to determine its effects on students. Whereas PjBL can also be used as a model to produce new information and experimental tools with the right method. This research is a laboratory experimental study that aims to produce an experimental device to determine the refractive index of various materials using refractive and perfect reflection methods. To complete this research, the team followed the steps of PjBL which consisted of 7 stages, namely Challenging Problems or Questions, Sustained Inquiry, Authenticity, Student Voice and Choice, Reflection, Critique and Revision, and Public Product. By following the PJBL stages, the team succeeded in producing an experimental device with good results. The results show that the experimental device produced works well and is able to determine the refractive index of the material with a fairly accurate value where the error value is below 1%. From this process also, the team acquired more skills, namely critical thinking, problem-solving, communication and collaboration.